2009
DOI: 10.1177/0145721708328597
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Evidence-Based Guidelines for Treating Hyperlipidemia in Children With Type 1 Diabetes

Abstract: In this case study, evidence-based nutrition guidelines have been evaluated and reviewed to demonstrate heart-healthy eating for children with hyperlipidemia and type 1 diabetes. It is known that approximately 40% to 50% of children with elevated lipids will continue to have abnormal lipids into adolescence and early adulthood. Therefore, early screening is recommended by the AHA to track lipid changes during childhood and adolescence and to begin treating abnormal LDL-C levels to prevent the development of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Cholesterol feeding has been often used to elevate serum or tissue cholesterol levels to assess hypercholesterolemia-related metabolic disturbances in different animal models. [1,2,19] Rats fed with a diet supplemented with cholesterol 2%, sodium cholate 1%, sucrose 48%, peanut oil, methionine 4%, and 47% normal laboratory feed for 30 days served as the experimental model. This is in accord with the previous finding reported by Yoon et al, 2008, who showed that feeding rats with high cholesterol diet (HCD) for 7 days induced hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol feeding has been often used to elevate serum or tissue cholesterol levels to assess hypercholesterolemia-related metabolic disturbances in different animal models. [1,2,19] Rats fed with a diet supplemented with cholesterol 2%, sodium cholate 1%, sucrose 48%, peanut oil, methionine 4%, and 47% normal laboratory feed for 30 days served as the experimental model. This is in accord with the previous finding reported by Yoon et al, 2008, who showed that feeding rats with high cholesterol diet (HCD) for 7 days induced hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…About 20% reduction of blood cholesterol level can decrease about 31% of CHD incidence and 33% of its mortality rate. [2][3][4][5][6] Lipids play out some significant capacities in body. In addition, hyperlipidemia is induced by secondary effect of diabetes; therefore, the agent having some antioxidant and antidiabetic effect also showed favorable effect to hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…A 20% reduction of blood cholesterol level can decrease by about 31% of CHD incidence, and 33% of its mortality rate. [2][3][4][5][6] Lipids play out some significant capacities in the body. Also, hyperlipidemia is induced by the secondary effect of diabetes.…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%
“…33,34 Hyperlipidemia is defined in children and adolescents with diabetes as having a LDL greater than 100 mg/dL. 35 Children with double diabetes are also at risk for having low HDL of less than 40 mg/dL and a TG level greater than 100 mg/dL in children younger than 10 years, and greater than 130 mg/dL in children aged 10 to 19 years. 25 Medical nutrition therapy for abnormal lipids has been well documented to reduce LDL cholesterol by 30%.…”
Section: Hyperlipidemiamentioning
confidence: 99%